Circadian screening of neutrophils identifies therapeutic targets in multiple sclerosis - Francesco De Virgiliis; Coline Barnoud; Wenyan He; Qun Zeng; Robert Pick; Tianyue Sun; Stéphane Jemelin; Valeria Maria Oliva; Tiphaine Furlan; Carmen Picon-Muñoz; Doron Merkler; Christoph Scheiermann (Proceedings of the National Academy of Sciences, 2026)
Circadian rhythms are intrinsic time-keeping mechanisms that play a critical role in tuning immunity. Here, we investigated the impact of circadian rhythms on the pathogenesis of experimental autoimmune encephalomyelitis (EAE), a mouse model for multiple sclerosis (MS). We demonstrate that circulating neutrophils in blood significantly increase early in EAE, prior to symptoms onset. Importantly, we found that these cells infiltrate the central nervous system (CNS) in a time-of-day (ToD)-dependent manner, with increased infiltration at the onset of the behavioral active phase of the mice (evening). Transcriptomic analysis of CNS-infiltrating neutrophils revealed distinct ToD-dependent gene expression profiles, which identified Formyl peptide receptor 2 (FPR2) as a potential therapeutic candidate, since pharmacological inhibition of FPR2 led to reduced EAE disease severity. Furthermore, combinatorial treatment with a drug that targets VLA-4 (used in clinical practice under the trade name Natalizumab to treat MS) led to additive effects, substantially reducing EAE symptoms. Together, these findings highlight the importance of circadian immune cell dynamics during EAE development and provide a characterization of the circadian immune landscape in an animal model of MS, identifying potential targets for MS therapies.